2015
DOI: 10.1111/rec.12226
|View full text |Cite
|
Sign up to set email alerts
|

Loss of biodiversity and hydrologic function in seasonal wetlands persists over 10 years of livestock grazing removal

Abstract: Ecological restoration provides a means to increase biodiversity in ecosystems degraded by natural and human-induced changes. In some systems, disturbances such as grazing can be key factors in the successful restoration of biodiversity and ecological function, but few studies have addressed this experimentally, especially over long time periods and at landscape scales. In this study, we excluded livestock grazing from plots within a grassland landscape containing vernal pools in the Central Valley of Californ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 24 publications
7
41
1
Order By: Relevance
“…Our results support a long‐term vernal pool cattle grazing study that demonstrated how grazing can promote native species growth and decrease invasive species (Marty , ). Extending the advantages of grazing found in these studies (Marty , ) to our findings, it is possible that livestock grazing decreases aboveground plant biomass and subsequently reduces the litter layer, or thatch accumulation, that would inhibit native species success. Thatch reduction through grazing has also been shown to increase inundation duration (Marty ) and even mitigate the effects of decreased precipitation due to climate change (Pyke & Marty ).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our results support a long‐term vernal pool cattle grazing study that demonstrated how grazing can promote native species growth and decrease invasive species (Marty , ). Extending the advantages of grazing found in these studies (Marty , ) to our findings, it is possible that livestock grazing decreases aboveground plant biomass and subsequently reduces the litter layer, or thatch accumulation, that would inhibit native species success. Thatch reduction through grazing has also been shown to increase inundation duration (Marty ) and even mitigate the effects of decreased precipitation due to climate change (Pyke & Marty ).…”
Section: Discussionsupporting
confidence: 86%
“…Extending the advantages of grazing found in these studies (Marty , ) to our findings, it is possible that livestock grazing decreases aboveground plant biomass and subsequently reduces the litter layer, or thatch accumulation, that would inhibit native species success. Thatch reduction through grazing has also been shown to increase inundation duration (Marty ) and even mitigate the effects of decreased precipitation due to climate change (Pyke & Marty ). These studies (Pyke & Mary ; Marty , ) support grazing as a successful management strategy for preventing the invasive species positive feedbacks this study has illustrated.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The relationship between animal grazing and freshwater ecosystems is complicated. Because grasslands can require natural disturbance or active management to prevent succession to forest, grazing at certain levels and times of the year may be an appropriate and necessary activity in some systems, and can contribute to maintaining native freshwater biodiversity (Bloom, Howerter, Emery, & Armstrong, 2013;Marty, 2015;Mester, Szalai, Mero, Puky, & Lengyel, 2015); however, overgrazing can have impacts on sediment and nutrient delivery, as well as on hydrology. Furthermore, livestock congregating in riparian zones and entering streams in order to cross or gain access to water can have direct impacts on stream banks and can introduce bacterial and nutrient contaminants into the water, as well as increase sediments (Fitch & Adams, 1998).…”
Section: Ranching Best Management Practicesmentioning
confidence: 99%